Unveiling the Relationship of Zoomer Generation Learning Preferences and Mathematical Conceptual Understanding - Maharani Maharani; Mutia Mutia; Anisya Septiana (Journal of Instructional Mathematics, 2026)
This study aims to know relationship between Gen Z's mathematics learning preferences and their ability to understand mathematical concepts. The research method used a quantitative approach with a correlational study design. The research population consisted of 199 eighth-grade students at MTs Baitul Makmur, and through simple random sampling, a sample of 34 students. The instruments used were questionnaires and tests. The data analysis technique employed was the product-moment correlation test. The research results indicate that: (1) Gen Z students prefer learning in pairs (70.52%) and asking questions directly to the teacher (69.99%) while passive methods such as rewriting (51.17%) and listening to recordings (52.64%) are less preferred as they are considered less effective; (2) Gen Z students are fairly good at using mathematical steps (approximately 69.11%), but still struggle to understand the key aspects of the concepts (60.29%), so Gen Z students understand how it works more than its meaning; (3) There is a significant relationship between learning preferences (X) and mathematical concept understanding ability (Y), with a correlation coefficient of 0.629, thus falling into the category of a strong relationship. The coefficient of determination of 39.43% indicates that learning preferences contribute moderately to students' conceptual understanding ability.